2014
DOI: 10.1148/radiol.14131856
|View full text |Cite
|
Sign up to set email alerts
|

Potholes and Molehills: Bias in the Diagnostic Performance of Diffusion-Tensor Imaging in Concussion

Abstract: Purpose:To investigate the extent of bias in a clinical study involving "pothole analysis" of diffusion-tensor imaging (DTI) data used to quantify white matter lesion load in diseases with a heterogeneous spatial distribution of pathologic findings, such as mild traumatic brain injury (TBI), and create a mathematical model of the bias. Materials and Methods:Use of the same reference population to define normal findings and make comparisons with a patient group introduces bias, which potentially inflates report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 23 publications
2
40
0
Order By: Relevance
“…Thus, the bulk of studies examining military blast mTBI have included individuals with both primary blast exposure and additional secondary and tertiary injuries. These studies have generally shown decreases in white matter integrity both in the subacute (Mac Donald et al, 2011) and chronic phase (Davenport et al, 2012; Hayes et al, 2015; Jorge et al, 2012; Mac Donald et al, 2011; Morey et al, 2013), similar to the civilian mTBI literature (but see Bazarian et al, 2013; Levin et al, 2010; Watts et al, 2014). However, findings of greater neurologic deficits in individuals exposed to combat-related mTBI than civilian mTBI (Ruff et al, 2012) provide some evidence for increased noxious effects due to blast and suggest the need for further studies comparing blast-induced mTBI and civilian TBI.…”
Section: Tbi-associated Structural Connectivity Abnormalitiessupporting
confidence: 64%
“…Thus, the bulk of studies examining military blast mTBI have included individuals with both primary blast exposure and additional secondary and tertiary injuries. These studies have generally shown decreases in white matter integrity both in the subacute (Mac Donald et al, 2011) and chronic phase (Davenport et al, 2012; Hayes et al, 2015; Jorge et al, 2012; Mac Donald et al, 2011; Morey et al, 2013), similar to the civilian mTBI literature (but see Bazarian et al, 2013; Levin et al, 2010; Watts et al, 2014). However, findings of greater neurologic deficits in individuals exposed to combat-related mTBI than civilian mTBI (Ruff et al, 2012) provide some evidence for increased noxious effects due to blast and suggest the need for further studies comparing blast-induced mTBI and civilian TBI.…”
Section: Tbi-associated Structural Connectivity Abnormalitiessupporting
confidence: 64%
“…To summarize: clusters of voxels with abnormal values (e.g., z-scores beyond a given threshold) are calculated at the subject-specific analysis level before they are compared between groups. Although this approach has shown promise in adult and pediatric DTI studies of mTBI (Jorge et al 2012; Ling et al 2012; Mayer et al 2012; Miller et al 2016), the absence of cross-validation methods (e.g., leave-one-out; see Methods) in those studies raises the risk of bias (Mayer et al 2014; Watts et al 2014). …”
mentioning
confidence: 99%
“…In addition, the size of the potholes was considerably larger than those in the EOS group. Second, concern has surface recently over potential bias that can be associated with the pothole approach when the sample size for the control group is small [70]. While this bias clearly applies for small cluster sizes, it is not necessarily true for larger cluster sizes of contiguous voxels.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the children and adolescents with OCD and the controls had nearly a perfect overlap, which would not be expected in the presence of bias unless the group of children and adolescents with OCD has, on average, less WM potholes than the controls. When bias correction was applied as suggested by Watts et al [70], the EOB group had a significantly greater number and volume of potholes, whereas the OCD group had significantly fewer potholes compared to controls.…”
Section: Discussionmentioning
confidence: 99%